(untitled) (Global Journal of Science Frontier Research, 2024)
Climate change is a highly complex global conflict that implies unequal environmental social and economic consequences which is why it is presented as one of the great challenges of today s society To meet the climate change goals of reducing greenhouse gas emissions changes in social structures are necessary that require the participation of the general public This article analyzes the perceptions of Asunci n society about climate change through the application of the survey questionnaire with open and close questions The results show that seven out of ten people in Asunci n have heard about climate change they largely indicated the impacts of climate change such as high temperatures these perceptions are related to increases in average temperature in the region The population of Asunci n perceives that climate change is already occurring in the country the majority pointed to citizens as responsible for applying the solutions However there is concern about climate change driven by the perception of danger to geographically and temporally distant people making it difficult to take action to mitigate climate change and to reactively or proactively adapt to climate change